The diverse cellular responses of the choroid plexus during infection of the central nervous system - Lauer, Alexa; Tenenbaum, Tobias; Schroten, Horst; Schwerk, Christian (American journal of physiology. Cell physiology, 2018)
The choroid plexus (CP) is responsible for the production of a large amount of the cerebrospinal fluid (CSF). As a highly vascularized structure, the CP also presents a significant frontier between the blood and the central nervous system (CNS). To seal this border, the epithelium of the CP forms the blood-CSF barrier, one of the most important barriers separating the CNS from the blood. During the course of infectious disease, cells of the CP can experience interactions with intruding pathogens, especially when the CP is used as gateway for entry into the CNS. In return, the CP answers to these encounters with diverse measures. Here, we will review the distinct responses of the CP during infection of the CNS, which include engaging of signal transduction pathways, the regulation of gene expression in the host cells, inflammatory cell response, alterations of the barrier, and, under certain circumstances, cell death. Many of these actions may contribute to stage an immunological response against the pathogen and subsequently help in the clearance of the infection.
Gesehen am 25.09.2018